ANALISIS LAJU KOROSI PADA BAJA STAINLESS STEEL 304 YANG MENGALAMI PENGELASAN DAN BENDING 90 DERAJAT PADA AIR LAUT - Agus Umartono; Mochammad Miftachul Choiri (Wahana Teknik, 2022)
Stainless steel or stainless steel is a metal that is widely used in the industrial world. One of them is the austenitic stainless steel group due to its corrosion resistance, weldability and ease of shaping, making it widely used in industry. Stainless steel that is included in the food grade category is stainless steel with a composition of 18/8 or 18/10. The meaning of this code indicates the composition of chromium and nickel content. Samples were immersed in seawater for 7 weeks. The study used 10 samples, namely sample 1 and sample 2 were samples that did not experience welding and did not experience bending, samples 3, 4, 5, and 6 were samples that experienced welding, and samples 7, 8, 9 and 10 were samples that experienced bending 90 °. From the 3 types of test methods, it can be concluded that those undergoing welding had a higher corrosion rate than the samples subjected to bending 90° and samples that were not welded and not subjected to bending had the lowest corrosion rates.